Kemampuan Menulis Teks Anekdot Siswa Kelas X SMA Negeri 1 Lembah Gumanti Dengan Menggunakan Media Gambar - Wiwi Astuti; Pebriani, Yulia; Samsiarni, Samsiarni (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
The purpose of this study was to describe the ability to write anecdotal texts using image media of grade X students of SMA Negeri 1 Gumanti Valley. This type of research is quantitative research with descriptive methods. The population of this study was grade X students of SMA N 1 Lembah Gumanti, Solok Regency. The sample of this study was class XE8 students totaling 33 students. The data collection technique in this study was carried out in 1 meeting. The data in this study is the performance score of the ability to write anecdotal texts of grade X students of SMA N 1 Gumanti Valley by Using Image Media. In analyzing the data is done in several steps, First, reading the results of students' work writing anecdotal texts. Second, correct and give scores according to the aspects studied. Third, scoring students' work based on the aspects studied. Based on the data, it can be seen that the ability to write anecdotal texts using Image Media of grade X students of SMA N 1 Gumanti Valley as a whole is classified as Sufficient (C) with an average of 53.79.